Prevention of Dengue Hemorrhagic Fever (DHF) by Planting Lemongrass at SMK 17 Agustus 1945 Surabaya - IGAA Noviekayati; Jeane Putri Amelia; Junike putri virgilia; Lia Zairoh Siska Mawaddah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus which is transmitted through the bite of the Aedes aegypti and Aedes albopictus mosquitoes. Dengue Hemorrhagic Fever (DHF) is caused by the dengue virus and is transmitted by the Aedes aegypti mosquito, which is characterized by a sudden fever of two to seven days without a clear cause, weakness or lethargy, restlessness, heartburn accompanied by signs of bleeding on the skin in the form of bleeding spots, bruising or rashes. sometimes nosebleeds, bloody stools, vomiting blood, decreased consciousness or shock. This PKM aims to provide detailed information about DHF and how to prevent DHF using lemon grass. After participating in this lesson, participants are expected to be able to understand what dengue is, the benefits of lemongrass and know how to plant lemongrass in their neighborhood. The method used in this research is to conduct counseling and distribute pretest and posttest. The results show that this community service program can increase students' knowledge by 64.3% related to the dangers of dengue fever, the benefits of lemongrass as a mosquito repellent plant and how to plant lemongrass correctly.